FORMULATION AND EVALUATION OF ORAL FAST DISINTEGRATING TABLET OF IBUPROFEN USING TWO SUPER DISINTEGRANTS - Purkayastha, Hrishav Das; Nath, Bipul (International Journal of Current Pharmaceutical Research, 2017)
Objective: The aim of the present investigation was to design and evaluate orally disintegrating tablet (ODT) of Ibuprofen, a NSAID drug used for the treatment of arthritis with a view to improve its oral bioavailability. The focus of the current study was to develop ODT of Ibuprofen using super disintegrants for ease of administration and its physicochemical characterization. Methods: Tablets were made from blends by direct compression method. All the ingredients were passed through mesh no. 80. All the ingredients were co-ground in a pestle motor. The resulting blend was lubricated with magnesium stearate and compressed into tablets using the Cadmach single punch (round shaped, 8 mm thick) machine. Results: Physicals parameters of the prepared tablets like Hardness, Weight variation, Friability, thickness, drug content etc. found within the limits. The disintegration time of prepared ODTs was in the range of 45 to 55 seconds. In vitro dispersion time was found to be 22 to 52 seconds which may be attributed to faster uptake of water due to the porous structure formed by super disintegrants. Short disintegration and faster release of ibuprofen were observed with Cross carmellose sodium as compared to sodium starch glycollate. Conclusion: It is concluded that F3 offered the relatively rapid release of Ibuprofen when compared with other formulations. The increase in the concentrations of super disintegrants may lead to increase in the drug release. The formulation prepared with cross carmellose sodium was offered the relatively rapid release of Ibuprofen when compared with other concentrations of both the super disintegrant. Â 